2008
DOI: 10.2105/ajph.2007.115931
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in Adolescent and Young Adult Smoking in the United States: Metapatterns and Implications

Abstract: Long-term patterns for adolescent and young adult cigarette smoking were decidedly nonlinear, and we found evidence of a cohort effect among young adults. Continued strong efforts and a long-term societal commitment to tobacco use prevention are needed, given the unprecedented declines in smoking among most subpopulations since the mid- to late 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 45 publications
5
72
0
Order By: Relevance
“…the 1990s); and this finding is more prominent among younger adolescents (8th and 10th graders) 26 . However, as students age, trends of boys using cigarettes at higher rates emerge, with 12th grade boys having used at higher rates than females since the late 1980s 26 . The finding that female adolescents now use hookah at higher rates than males, a reversal from the findings of recent years, under scores the importance of frequently re-evaluating the changing landscape of tobacco use in the US.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…the 1990s); and this finding is more prominent among younger adolescents (8th and 10th graders) 26 . However, as students age, trends of boys using cigarettes at higher rates emerge, with 12th grade boys having used at higher rates than females since the late 1980s 26 . The finding that female adolescents now use hookah at higher rates than males, a reversal from the findings of recent years, under scores the importance of frequently re-evaluating the changing landscape of tobacco use in the US.…”
Section: Discussionmentioning
confidence: 91%
“…In the US, adolescent females have historically used cigarettes at higher rates than males at different points in time (i.e. the 1990s); and this finding is more prominent among younger adolescents (8th and 10th graders) 26 . However, as students age, trends of boys using cigarettes at higher rates emerge, with 12th grade boys having used at higher rates than females since the late 1980s 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies that examine trends in youth smoking have suggested that the increase in adolescent smoking prevalence during the early and mid 1990s can be attributed to intensive tobacco-industry promotional efforts targeted at youth, including price manipulations and surrogate marketing, 15 while the decline through 2003-2004 coincided with increased tobacco control strategies such as price increases and counter-advertising directed at adolescents. 15,16 Nonetheless, the tobacco industry continues to market to young smokers; studies have suggested that the recent leveling off in previous adolescent smoking declines may be due to effects of the tobacco industry's increased spending on marketing and promotions (ie, price discounting to blunt the effect of excise taxes increases on pricesensitive smokers) (Fig.…”
Section: Patterns Of Tobacco Use In Youthmentioning
confidence: 99%
“…15,16 Nonetheless, the tobacco industry continues to market to young smokers; studies have suggested that the recent leveling off in previous adolescent smoking declines may be due to effects of the tobacco industry's increased spending on marketing and promotions (ie, price discounting to blunt the effect of excise taxes increases on pricesensitive smokers) (Fig. 2) coincident with declines in funding for comprehensive tobacco-control programs.…”
Section: Patterns Of Tobacco Use In Youthmentioning
confidence: 99%